Tingkat Kebugaran Jasmani dan Prestasi Akademik Peserta Didik SMPN 1 Batusangkar Kabupaten Tanah Datar - Aldo Amri; Khairuddin Khairuddin; Deswandi Deswandi; Berto Apriyano (Mutiara Pendidikan dan Olahraga, 2025)
The research problem is that students have low physical fitness. They appear lethargic, unmotivated, and struggle to focus on memorizing lessons. Additionally, many students are unable to complete several physical tests in physical education classes. Furthermore, the average student scores do not meet the learning objective criteria. This study uses a quantitative descriptive research method. The population consists of 787 students from grades VII, VIII, and IX of SMP Negeri 1 Batusangkar, Tanah Datar Regency. The sample was selected using the Proportionate Stratified Random Sampling technique, resulting in a sample size of 39 students. Data collection was conducted through physical fitness tests and students' average report card scores. The study found that, based on correlation analysis, the obtained r-value (rhitung) was 0.97, while the critical r-value (rtabel) at a significance level of α = 0.05 was 0.316. This indicates a significant relationship between physical fitness and academic achievement. In other words, the better a student's physical fitness, the better their academic performance, as confirmed by this study.